On geometry of isophote curves in Galilean space - Yuzbasi, Zuhal Kucukarslan; Yoon, Dae Won (Amer Inst Mathematical Sciences-Aims, 2021)
In this paper, we introduce isophote curves on surfaces in Galilean 3-space. Apart from the general concept of isophotes, we split our studies into two cases to get the axis d of isophote curves lying on a surface such that d is an isotropic or a non-isotropic vector. We also give a method to compute isophote curves of surfaces of revolution. Subsequently, we show the relationship between isophote curves and slant (general) helices on surfaces of revolution obtained by revolving a curve by Euclidean rotations. Finally, we give some characterizations for isophote curves lying on surfaces of revolution.
Keywords: Galilean space; isophote curve; surfaces of revolution